2015
DOI: 10.1038/ncomms9590
|View full text |Cite
|
Sign up to set email alerts
|

Wave-driven butterfly distribution of Van Allen belt relativistic electrons

Abstract: Van Allen radiation belts consist of relativistic electrons trapped by Earth's magnetic field. Trapped electrons often drift azimuthally around Earth and display a butterfly pitch angle distribution of a minimum at 90° further out than geostationary orbit. This is usually attributed to drift shell splitting resulting from day–night asymmetry in Earth's magnetic field. However, direct observation of a butterfly distribution well inside of geostationary orbit and the origin of this phenomenon have not been provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
178
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 58 publications
(68 reference statements)
3
178
1
Order By: Relevance
“…Wave‐particle interactions causing loss and acceleration of electrons in the Earth's radiation belts have been extensively studied since the beginning of the space era (Imhof et al, ; Millan & Thorne, ; Shprits, Elkington, et al, ; Shprits, Subbotin, et al, ; Thorne, ; Thorne & Kennel, ; Xiao et al, , ). Recently, particular attention has been paid to the dynamics of very energetic ultrarelativistic electrons (energy above ∼1–2 MeV) (e.g., Baker, Kanekal, Hoxie, Henderson, et al, ; Shprits et al, ; , Xiao et al, ). However, major mechanisms controlling this population are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Wave‐particle interactions causing loss and acceleration of electrons in the Earth's radiation belts have been extensively studied since the beginning of the space era (Imhof et al, ; Millan & Thorne, ; Shprits, Elkington, et al, ; Shprits, Subbotin, et al, ; Thorne, ; Thorne & Kennel, ; Xiao et al, , ). Recently, particular attention has been paid to the dynamics of very energetic ultrarelativistic electrons (energy above ∼1–2 MeV) (e.g., Baker, Kanekal, Hoxie, Henderson, et al, ; Shprits et al, ; , Xiao et al, ). However, major mechanisms controlling this population are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, further studies have shown that space plasma waves, including magnetosonic waves, can significantly affect the dynamics of the magnetospheric particles (e.g., Horne et al 2007;Xie et al 2007;Li et al 2008;Gu et al 2011;Chang et al 2013;Xiao et al 2015). Based on the Cluster wave observations, Horne et al (2007) established a model of magnetosonic waves for adoption to compute their quasi-linear bounce-averaged diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the pitch angle scattering effect of magnetosonic waves is weak for electron precipitation losses, but the momentum diffusion is relatively strong for electron energization. Xiao et al (2015) found that the combined effect of magnetosonic waves and chorus waves with radiation belt electrons can lead to the diffusion of electrons from high pitch angles of ~90° to intermediate pitch angles, resulting in "butterfly-like'' electron distributions (Gannon et al 2007). The significance of Landau resonant scattering by equatorial magnetosonic waves has been further recognized to account for the formation of energetic electron butterfly distributions in the inner magnetosphere from the outer edge of the inner zone to much higher L-shells (e.g., Li et al 2016a, b;Ma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are also cases where the narrow bands are observed at off‐harmonic frequencies, often with frequency spacings substantially deviating from integer multiples of Ω p , or the frequency spectrum does not exhibit any discrete bands at all, but broadband structures; examples of these cases have been recently reported by Posch et al []. One explanation for the odd harmonicity of fast magnetosonic waves is that the waves can propagate across the field lines [ Kasahara et al , ; Horne et al , ; Chen and Thorne , ; Xiao et al , , ]. Although they were excited at the harmonics of Ω p in the source region, the wave frequencies normalized to the local Ω p vary, as the waves propagate radially.…”
Section: Introductionmentioning
confidence: 99%